Synthesis and molecular modeling of some novel hydroxypyrone derivatives as antidermatophytic agents - TÜRE, ASLI (My University, 2022)
Dermatophytes are pathogenic fungi, comprising the major cause of superficial fungal infections called dermatophytes. Although they infect keratinized tissues such as skin, nail, and hair, invasive serious infections may occur in immunocompromised patients. However, current antifungal drugs show considerable drawbacks, such as toxicity and multiple drug resistance, compelling and directing researches for new antidermatophyte agents. Herein, a series of hydroxypyrone bearing compounds inspired from the natural metabolite kojic acid was reported. Their antidermatophytic effects of the compounds against Microsporum gypseum, Trichophyton mentagrophytes var. erinaceid, and Epidermophyton floccosum were evaluated. The cytotoxicity of the compounds on healthy (MRC-5) and carcinogenic (He-La) cell lines was also investigated, and their cytopathogenic effects were expressed as maximum non-toxic concentrations. According to the activity studies, compounds 10 and 22 were found as the most promising antidermatophytic agents (MIC: 2 mu g/ml), exhibiting comparable effect with that of griseofulvin (MIC: 0.5-1 mu g/ml) and terbinafine (MIC: 0.125-0.5 mu g/ml) which are the most widely used agents for treating mycoses caused by dermatophytes. Molecular docking analysis of the most active compounds, compound 10 and compound 22, with homology model of beta-tubulin protein was carried out to investigate the possible binding conformation of the compounds in the targeted macromolecule.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; KİMYA, ORGANİK; Temel Bilimler (SCI); CHEMISTRY, ORGANIC; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Organik Kimya; Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); Organic Chemistry; General Chemistry; Physical Sciences